Photosystem II The Light-Driven Water:Plastoquinone Oxidoreductase - Wydrzynski, T.; Wydrzynski, T.; Satoh, Kimiyuki.; Satoh, Kimiyuki. (Advances in Photosynthesis and Respiration, Including Bioenergy and Related Processes, 2005)
Dedicated to the memory of one of the early pioneers in this field of research, Professor Gerald T. Babcock, the 34 inclusive chapters of the present volume cover all major aspects of the molecular biology, biochemistry, biophysics and physiology of Photosystem II. The chapters were variously authored by a total of 75 scientific experts from leading research centers in Europe, North America, Asia and Australia, making the book a truly international effort. The book is divided into several parts which detail the protein constituents, functional sites, tertiary structure, molecular dynamics and mechanisms of subunit assembly and homeostasis. The book ends with a comparison of Photosystem II structure and function with other related enzymes and bio-mimetic systems. Since the unique water-splitting chemistry catalyzed by Photosystem II leads to the production of pure oxygen gas and the potential for making hydrogen gas, a primary goal of this book is to provide a molecular guide to future protein engineers and bio-mimetic chemists in the development of appropriate biocatalysts for the generation of clean, renewable energy from sunlight and water.